Propuestas teóricas y metodológicas para descifrar riesgos y desastres desde las Ciencias Sociales - Toscana Aparicio, Alejandra (Universidad de San Buenaventura - Cali, 2017)
In the middle of the 20th century Social Sciences became interested in the study of risks and disasters which had been dominated by the Earth Sciences and engineering. The objective of this text is to present an overview of the theoretical and methodological proposals that have contributed to the understanding of the processes of risk-disaster from social sciences. The text is divided into two parts: the first part presents four ways of conceiving these processes, risk as a result of the interaction of society-nature, risk in relation to the vulnerability of society, risk as a characteristic of modernity and risk from its symbolic dimension. The second part addresses some methodologies used to study risks and disasters and to understand its meaning, taking as a starting point that risk is a social construction.